High-pressure hot-pressing mold surface coating and preparation method thereof

By depositing Cr-CrN-TiAlN coating on the surface of H13 steel substrate and processing it in a high-voltage electric field, the problem of insufficient bonding force between the coating and the substrate is solved, and the service life and performance of the mold are improved under high temperature and high pressure.

CN120575145AActive Publication Date: 2025-09-02XIAN CARBONFENG NEW MATERIAL TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202511088715.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-09-02
Estimated Expiration
2045-08-05

AI Technical Summary

Technical Problem

The interface bonding force between the surface coating of the existing hot press mold and the substrate is insufficient, and it is easy to fail under high temperature and high pressure, affecting the mold life and workpiece quality.

Method used

The Cr layer, CrN layer and TiAlN layer were deposited on the surface of the H13 steel substrate by magnetron sputtering method, and treated in a high-voltage electric field to form a Cr-CrN-TiAlN composite coating, which promotes the diffusion of interface elements and chemical bond formation through electric field forces, and optimizes the microstructure of the coating.

Benefits of technology

The interface bonding strength between the coating and the substrate is improved, and the service performance and service life of the mold under high-pressure and strong hot pressing conditions are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120575145A_ABST
    Figure CN120575145A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of surface engineering, and particularly discloses a high-pressure hot-pressing mold surface coating and a preparation method thereof. The preparation method of the high-pressure hot-pressing mold surface coating comprises the following steps: (1) pretreating an H13 steel substrate; (2) sequentially depositing a Cr layer, a CrN layer and a TiAlN layer on the surface of the pretreated H13 steel by adopting a magnetron sputtering method to form a Cr-CrN-TiAlN composite coating; and (3) the coated substrate is placed in a high-voltage electric field to be treated, and the high-pressure hot-pressing mold surface coating is obtained. According to the high-pressure hot-pressing mold surface coating, the binding force of a base body and the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of surface engineering technology, and more specifically, to a high-pressure hot-pressing mold surface coating and a preparation method thereof. Background Art

[0002] As the manufacturing industry evolves towards higher-end, more sophisticated production, hot stamping dies are increasingly being used in aerospace, automotive, and electronic packaging. Under high-temperature and high-pressure conditions, H13 steel stands out as a material for high-pressure hot stamping dies due to its excellent overall performance. Its alloying elements, such as Cr, Mo, and V, form stable carbides, imparting excellent hardenability and high-temperature strength. Its yield strength remains ≥1000 MPa at temperatures between 500 and 600°C, and it can withstand transient pressures exceeding 1500 MPa, effectively resisting plastic deformation under high pressure. Compared to traditional materials, H13 steel offers longer service life, lower maintenance costs, and more stable forming accuracy in high-pressure hot stamping applications such as hot forging and powder metallurgy. However, under high-pressure hot stamping conditions, H13 steel is susceptible to surface wear due to friction with the billet, oxidation and die sticking in high-temperature environments, and thermal fatigue cracking caused by repeated heating and cooling, shortening die life and compromising workpiece quality.

[0003] Surface coating technology has become a key means of improving mold performance. Applying high-hardness, high-modulus ceramic coatings (such as TiN, ZrB2-SiC), metal-ceramic composite coatings (Ti(C, N)-Ni), or functionally gradient coatings to the mold surface can significantly improve the compressive strength and wear resistance of the mold surface. For example, patent application publication number CN102650029A discloses a method for preparing a nano-ceramic composite coating material for a hot-working mold surface, including steps for preparing a spray feed, pretreating an H13 steel substrate, preparing a transition layer, and preparing a nano-ceramic composite layer. In this patent application, during the plasma spraying process, the interface between the nickel-clad aluminum transition layer and the H13 steel substrate forms only a localized micrometallurgical bond (e.g., a Ni-Fe solid solution), but the overall bond is primarily mechanical. Due to the differences in the physical and chemical properties of the metal and ceramic (e.g., poor wettability and difficulty in element diffusion), the interface between the ceramic layer and the transition layer has almost no metallurgical bond, relying solely on mechanical interlocking and the surface roughness of the transition layer to maintain the bond. This makes it susceptible to failure under cyclic thermal stress and mechanical loads. Therefore, the development of new coating materials and preparation processes with high compressive strength, excellent thermal stability and strong interface bonding between the coating and the substrate is of great significance to improving the service performance and service life of hot pressing molds. Summary of the Invention

[0004] In order to improve the interface bonding strength between the prepared coating and the substrate, the present application provides a high-pressure hot pressing mold surface coating and a preparation method thereof.

[0005] In the first aspect, the present application provides a method for preparing a surface coating of a high-pressure hot-pressing mold, which adopts the following technical solution: A method for preparing a surface coating of a high-pressure hot-pressing mold comprises the following steps: (1) Pretreatment of H13 steel substrate; (2) Magnetron sputtering was used to deposit Cr layer, CrN layer and TiAlN layer in sequence on the pretreated H13 steel surface to form a Cr~CrN~TiAlN composite coating; (3) The coated substrate is placed in a high-voltage electric field for treatment to obtain a high-pressure hot pressing mold surface coating.

[0006] By adopting the above technical solution, on the one hand, the electric field force drives the directional migration of charged defects in the coating, which helps to release residual stress and promotes the diffusion of interface elements to form a transition layer with a gentle composition gradient, thereby reducing the interface brittleness caused by stress concentration and composition mutation; on the other hand, the electric field can optimize the microstructure of the coating. By reducing pores and refining grains to increase density, mechanical bite is enhanced; in addition, it may also promote the formation of stronger chemical bonds at the interface, thereby upgrading simple mechanical bonding to a synergistic effect of chemical and mechanical bonding, and ultimately improving the interfacial bonding strength between the substrate and the coating.

[0007] Preferably, step (3) is specifically as follows: placing the coated substrate in a high-voltage electric field consisting of two parallel metal plates, one of which is grounded and the other is connected to a high-voltage electric field generator, and the distance between the coating surface on the substrate and the metal plates is greater than 1 mm.

[0008] By adopting the above technical solution, parallel metal plates can form a uniform DC electric field between the plates, ensuring that the interface between the coating and the substrate is subjected to a stable electric field; the coating surface does not contact the plate, which can prevent local discharge, short circuit or mechanical friction between the plate and the coating from damaging the coating, while ensuring that the electric field can penetrate the coating and act on the interface; in addition, the distance between the coating surface on the substrate and the metal plate is greater than 1 mm, which can avoid air breakdown of the coating due to too small a distance.

[0009] Preferably, the distance between the coating surface on the substrate and the metal electrode is 2-4 mm, the voltage of the high-voltage electric field is 5-50 kV, and the treatment time is 5-30 min.

[0010] By adopting the above technical solution, the electric field needs to provide sufficient driving force to promote the directional migration of charged defects in the coating and achieve effective release of residual stress; if the voltage is too low, the defect migration power is insufficient, the stress is difficult to relieve, and the interface bonding cannot be improved; at the same time, the electric field-assisted diffusion of interface elements needs to overcome the energy barrier of atomic migration, and the electric field voltage needs to reach a level that can reduce the diffusion activation energy to promote diffusion at a lower temperature and form an effective transition layer. If the voltage is insufficient, the diffusion effect is weak and a gradient interface cannot be formed; on the contrary, when the voltage is too high, defects such as micropores and cracks in the coating or local strong electric fields generated due to electric field distortion will trigger stress concentration, leading to defect diffusion and even coating peeling, destroying the coating and substrate structure.

[0011] The treatment time must ensure sufficient element diffusion and stress release. If it is too short, the interface diffusion layer will not be formed and the residual stress release will be incomplete. If the treatment time is too long, it will lead to excessive diffusion, and the Cr, Ti, and Al in the coating will migrate to the substrate in large quantities, destroying the coating's own composition and structure, or accumulating additional stress due to the continuous electric field, which will weaken the bonding.

[0012] If the distance between the coating surface on the substrate and the metal plate is too small, discharge between the substrate and the plate will occur, causing local damage; if the distance is too large, a higher voltage will be required to maintain effective strength, which will not only increase the equipment load, but also cause uneven intensity distribution due to electric field divergence, weakening the driving effect on interface defect migration and element diffusion.

[0013] Preferably, in step (3), the processing environment during the high-voltage electric field treatment is an inert gas atmosphere with a gas pressure of 20-30 Pa.

[0014] By adopting the above technical solution, an inert gas atmosphere is selected during treatment, which can effectively isolate oxygen and impurities, prevent oxidation reactions between easily oxidizable elements (such as Al, Ti, Cr) in the coating and the H13 steel substrate, and avoid the formation of a brittle oxide layer that hinders element diffusion. At the same time, it can inhibit impurities such as moisture and CO2 from reacting with the coating or substrate to form a brittle phase, ensuring the purity of the interface. In addition, the inert gas has high ionization energy, which can stabilize the high-voltage electric field distribution and reduce damage to the coating caused by arc discharge.

[0015] Preferably, the treatment temperature during the high voltage electric field treatment is 200-400°C.

[0016] By adopting the above technical solution, the tempering temperature of H13 steel must be lower than that of steel to avoid softening of the substrate due to overheating (reducing the supporting strength of the substrate); at the same time, it must be lower than the significant oxidation temperature of TiAlN. At the same time, low-temperature heat treatment assisted by an electric field can relieve the internal stress generated during the coating deposition process and refine the grains, thereby improving the hardness, wear resistance and anti-spalling properties of the coating.

[0017] Preferably, the specific method for pretreating the H13 steel substrate is: pretreating the surface of the H13 steel substrate by sequentially adopting supersonic sandblasting, ultrasonic shot blasting and plasma cleaning.

[0018] By adopting the above technical solutions, sandblasting provides the basis for mechanical bonding, shot peening refines the grains and strengthens the stress state, and cleaning eliminates interface barriers. The three form a progressive pretreatment system of "roughening-strengthening-cleaning", which constructs an ideal substrate on the H13 steel surface with mechanical anchoring, metallurgical diffusion, stress balance and high surface energy, providing a strong interface bonding foundation for subsequent coatings, significantly improving the service life of the mold under high pressure and strength conditions.

[0019] Preferably, a vacuum annealing strengthening treatment is further included, specifically, the mold treated with a high voltage electric field is treated at 300-400° C. in an inert atmosphere for 2-3 hours.

[0020] By adopting the above technical solution, high-voltage electric field treatment may induce lattice distortion due to the strong electric field force, generating local residual stress. At the same time, the rapid diffusion driven by the electric field may form a metastable phase. Annealing treatment can eliminate the residual stress caused by lattice distortion through atomic thermal motion, avoiding interfacial cracking caused by stress concentration. It promotes the transformation of the metastable phase into an equilibrium phase, enhancing the structural compatibility between the coating and the substrate. Thermal drive further strengthens the diffusion channels formed by the electric field pretreatment, allowing for more complete element diffusion and improving the metallurgical bonding at the interface.

[0021] Preferably, in step (2), the thickness of the Cr layer is 1.1-3.4 μm, the thickness of the CrN layer is 3.2-5.8 μm, and the thickness of the TiAlN layer is 4.9-7.2 μm.

[0022] By adopting this technical solution, the Cr layer serves to mitigate the physical property differences between the substrate and the subsequent top layer, and reduces interfacial stress through "metallurgical-grade" interfacial bonding. The Cr layer needs to be thick enough to cover the substrate and buffer stress, but not too thick to cause internal stress accumulation. The CrN intermediate layer serves to connect the Cr layer and the TiAlN outer layer. Its performance lies between the two, and a moderate thickness is required to achieve a performance transition, avoiding excessive thinness that causes interface abrupt changes or excessive thickness that causes stress concentration. The TiAlN outer layer is the "functional layer" of the coating, and its thickness affects bonding primarily through internal stress accumulation and a "pulling effect" on the underlying layer. It must be controlled within functional requirements to prevent excessive thickness from causing overall stress overload. By optimizing the thickness ratio of each layer, the interfacial compatibility of the Cr-CrN-TiAlN coating with the H13 steel substrate can be further improved.

[0023] Preferably, in step (2), the power of the Cr target used in the magnetron sputtering method is 200~300W, the power of the TiAl target is 300~500W, the distance between the target and the substrate is 8~12cm; the substrate temperature is 200~400℃, and the substrate bias is -50~-100V when depositing the Cr layer, the substrate bias is -80~-120V when depositing the CrN layer, and the substrate bias is -100~-150V when depositing the TiAlN layer.

[0024] By adopting the above technical solution, the target power determines the deposition rate and coating structure, the appropriate distance between the target material and the substrate can balance the particle energy and deposition uniformity, and the appropriate substrate temperature can not only ensure the crystallinity of the coating but also avoid substrate softening. The layered bias optimizes the stress distribution and interfacial bonding strength of each layer by regulating the ion bombardment intensity. These parameters interact to optimize the performance of the Cr-CrN-TiAlN coating and the H13 steel substrate.

[0025] In the second aspect, the present application provides a high-pressure hot-pressing mold surface coating, which adopts the following technical solution: A high-pressure hot-pressing die surface coating is prepared by using the above preparation method.

[0026] In summary, this application has the following beneficial effects: 1. The preparation method of this application uses magnetron sputtering to deposit a composite coating on the surface of H13 steel and then performs high-voltage electric field treatment. The high-voltage electric field can not only promote the diffusion of interface elements and form a transition layer, but also promote the formation of chemical bonds at the interface, thereby improving the bonding between the substrate and the coating.

[0027] 2. This application further improves the effect of the electric field on the coating and the substrate by optimizing the process parameters such as the electric field intensity, processing time, processing environment and processing temperature during high-voltage electric field treatment, thereby further improving the bonding between the two.

[0028] 3. This application also performs annealing treatment on the coating after high-voltage electric field treatment. The annealing treatment not only eliminates the lattice distortion caused by the high-voltage electric field, but also further strengthens the diffusion channel formed by the electric field pretreatment, thereby improving the metallurgical bonding of the interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a cross-sectional morphology of the surface coating of the high-pressure hot-pressing mold prepared in Example 12; Figure 2 This is the energy spectrum of the surface coating of the high-pressure hot pressing mold prepared in Example 12. DETAILED DESCRIPTION

[0030] The present application is further described in detail below with reference to the embodiments.

[0031] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0032] Example 1 This embodiment provides a method for preparing the surface coating of the high-pressure hot-pressing mold, comprising the following steps: (1) The H13 steel mold substrate was subjected to supersonic sandblasting with 20-40 μm Al2O3 abrasive, 0.6 MPa pressure, and 80 nm spray distance. The treatment time was 3 min, and the surface roughness of the H13 steel mold was obtained to be Ra=5-8 μm. Then, a 1 mm diameter WC-Co projectile was used, with a frequency of 20 kHz and an amplitude of 30 μm, for 10 min to obtain a nanocrystalline layer H13 steel mold with a surface of 50-100 nm. The treated H13 steel mold was fixed on the substrate holder of the vacuum chamber and connected to the cathode of the bias power supply. The Cr target and TiAl target required for coating were respectively fixed on the cathode of the evaporation source, and the distance between the mold and the target was 10 cm. At the same time, a mask was used to fit the non-cavity surface of the mold, and the base of the evaporation source was connected to the anode. The vacuum chamber door was closed, and the mechanical pump was started to evacuate the air to a pressure less than 0.1 Pa. Then the molecular pump was turned on to evacuate the air to a background vacuum less than 3×10 -4 Pa; turn on the substrate heating stage, raise the temperature to 300℃, and keep it warm for 30 minutes; then introduce Ar gas with a flow rate of 15sccm, adjust the vacuum chamber pressure to 0.4Pa; apply a negative bias voltage of 400V to the mold, turn on the auxiliary anode, and generate Ar + Particles bombard the mold surface and etch for 20 minutes; (2) Turn on the Cr target, introduce Ar gas, and maintain the working pressure in the vacuum chamber at 0.4 Pa. At the Cr target power of 250 W and the bias voltage of -80 V, deposit for 30 minutes to obtain a Cr transition layer with a thickness of 2.3 μm; continue to keep the Cr target open, keep introducing 20 sccm of Ar, and introduce 10 sccm of N2 into the vacuum chamber, maintain the pressure in the vacuum chamber at 0.4 Pa, at the Cr target power of 250 W and the bias voltage of -100 V, and deposit for 60 minutes to obtain To a CrN layer with a thickness of 4.6μm; turn off the Cr target, turn on the TiAl target, introduce 20sccm of Ar and 30sccm of N2, and maintain the working pressure in the vacuum chamber at 0.4Pa. At the TiAl target power of 400W and the bias voltage of -120V, deposit for 90min to obtain a TiAlN layer with a thickness of 6.1μm; after the deposition is completed, turn off the target power and gas, maintain the vacuum state of the vacuum chamber, cool it to below 100℃ with the furnace, fill it with Ar gas to normal pressure, and take out the mold; (3) A closed cavity made of polytetrafluoroethylene is used, and an electrode interface is reserved in the cavity; two metal plates are fixed in the center of the cavity in an upper and lower parallel manner with an insulating bracket, wherein the lower plate is connected to the external ground electrode through the cavity insulating sleeve via a grounding wire, and the wire of the other metal plate is connected to the high-voltage power supply through the insulating sleeve through the cavity wall, and the gas path interface is connected to a vacuum pump; the mold is placed in the middle of the two plates, specifically: the distance between the upper mold and the lower mold is 10 mm, and the two are fixed in the cavity by an insulating bracket; the cavity surface of the upper mold is opposite to the lower plate and the distance between the two is 2 mm, and a copper sheet with a thickness of 0.1 mm is fixed on the lower plate at one end, and the other end is pressed on the non-coated surface of the upper mold with an insulating clamp, and the cavity surface of the lower mold is opposite to the upper plate and the distance between the two is 2 mm; start the high-voltage power supply, set the voltage to 5kV, and continue the treatment for 30 minutes. After the treatment is completed, turn off the high-voltage power supply, open the cavity and take out the mold.

[0033] Example 2 This embodiment is basically the same as embodiment 1, except that: step (3) uses a closed cavity made of polytetrafluoroethylene, and an electrode interface is reserved in the cavity; the two metal plates are fixed in the center of the cavity in an upper and lower parallel manner by an insulating bracket, wherein the lower plate is connected to the external ground electrode through the cavity insulating sleeve via a grounding wire, and the wire of the other metal plate is connected to the high-voltage power supply through the insulating sleeve through the cavity wall, and the air path interface is connected to a vacuum pump; the mold is placed between the two plates, specifically: the upper mold and the lower mold are 10 mm apart, and the two are fixed in the cavity by an insulating bracket; the cavity surface of the upper mold is opposite to the lower plate and the distance between the two is 3 mm, and a copper sheet with a thickness of 0.1 mm is fixed to the lower plate at one end, and the other end is pressed against the non-coated surface of the upper mold with an insulating clamp, and the cavity surface of the lower mold is opposite to the upper plate and the distance between the two is 3 mm; the high-voltage power supply is started, the voltage is set to 30 kV, and the treatment is continued for 20 minutes. After the treatment is completed, the high-voltage power supply is turned off, the cavity is opened, and the mold is taken out.

[0034] Example 3 This embodiment is basically the same as embodiment 1, except that: step (3) uses a closed cavity made of polytetrafluoroethylene, and an electrode interface is reserved in the cavity; the two metal plates are fixed in the center of the cavity in an upper and lower parallel manner by an insulating bracket, wherein the lower plate is connected to the external ground electrode through the cavity insulating sleeve via a grounding wire, and the wire of the other metal plate is connected to the high-voltage power supply through the insulating sleeve through the cavity wall, and the air path interface is connected to a vacuum pump; the mold is placed between the two plates, specifically: the upper mold and the lower mold are 10 mm apart, and the two are fixed in the cavity by an insulating bracket; the cavity surface of the upper mold is opposite to the lower plate and the distance between the two is 4 mm, and a copper sheet with a thickness of 0.1 mm is fixed to the lower plate at one end and pressed against the non-coated surface of the upper mold with an insulating clamp at the other end, and the cavity surface of the lower mold is opposite to the upper plate and the distance between the two is 4 mm; the high-voltage power supply is started, the voltage is set to 50 kV, and the treatment is continued for 30 minutes. After the treatment is completed, the high-voltage power supply is turned off, the cavity is opened, and the mold is taken out.

[0035] Example 4 This embodiment is basically the same as embodiment 2, except that step (3) uses a closed cavity made of polytetrafluoroethylene, and an electrode interface, a gas path interface and a vacuum pumping port are reserved in the cavity; the gas path interface is connected to an argon purifier, and the vacuum pumping port is connected to a vacuum pump. A closed cavity made of polytetrafluoroethylene is used, and an electrode interface is reserved in the cavity; two metal plates are fixed in the center of the cavity in an upper and lower parallel manner using an insulating bracket, wherein the lower plate is connected to the external ground electrode through the cavity insulating sleeve through the grounding wire, and the wire of the other metal plate is connected to the external ground electrode through the grounding wire. The cavity wall is connected to the high-voltage power supply through an insulating sleeve, and the gas line interface is connected to a vacuum pump. The mold is placed between the two electrode plates. Specifically, the upper mold and the lower mold are 10 mm apart, and the two are fixed in the cavity by an insulating bracket. The cavity surface of the upper mold faces the lower electrode plate with a distance of 3 mm between them, and the cavity surface of the lower mold faces the upper electrode plate with a distance of 3 mm between them. A copper sheet with a thickness of 0.1 mm is fixed to the lower electrode plate at one end, and the other end is pressed against the non-coated surface of the upper mold with an insulating clamp. The vacuum pump is started and the pressure in the cavity is pumped to 1×10 -3 Pa, maintain for 5 minutes to eliminate residual air, turn off the vacuum pump and introduce argon until the pressure in the cavity is 25Pa, and stabilize for 10 minutes; start the high-voltage power supply, set the voltage to 30kV, and continue processing for 20 minutes. After the processing is completed, turn off the high-voltage power supply, open the cavity and take out the mold.

[0036] Example 5 This embodiment is basically the same as embodiment 4, except that step (3) uses a closed cavity made of polytetrafluoroethylene, and an electrode interface, a temperature measuring hole, a gas path interface and a vacuum pumping port are reserved in the cavity. The gas path interface is connected to an argon purifier, and the vacuum pumping port is connected to a vacuum pump. The armored heating wire is wrapped around the outside and matched with the embedded K-type thermocouple inside the cavity; the two metal plates are fixed in the center of the cavity in a parallel manner with an insulating bracket, wherein the lower plate is connected to the external ground electrode through the cavity insulating sleeve through the grounding wire, and the other plate is connected to the external ground electrode through the cavity insulating sleeve. The wires of the metal plates are connected to the high-voltage power supply through insulating sleeves through the cavity wall, and the gas line interface is connected to a vacuum pump. The mold is placed between the two plates. Specifically, the upper mold and the lower mold are 10 mm apart, and both are fixed in the cavity by insulating brackets. The cavity surface of the upper mold faces the lower plate with a minimum distance of 4 mm between them, and the cavity surface of the lower mold faces the upper plate with a minimum distance of 4 mm between them. A 0.1 mm thick copper sheet is fixed to the lower plate at one end, and the other end is pressed against the non-coated surface of the upper mold with an insulating clamp. Start the vacuum pump and pump the pressure in the cavity to 1×10 -3 Pa, maintain for 5 minutes to eliminate residual air, turn off the vacuum pump and introduce argon until the pressure in the cavity is 25Pa, stabilize for 10 minutes, increase the temperature to 300℃ at a rate of 10℃ / min, keep the temperature constant for 10 minutes, start the high-voltage power supply, set the voltage to 30kV, and continue the treatment for 20 minutes. After the treatment is completed, turn off the high-voltage power supply, keep the argon flowing, wait for the mold to cool naturally to room temperature, open the cavity and take out the mold.

[0037] Example 6 This embodiment is basically the same as embodiment 5, except that step (3) uses a closed cavity made of polytetrafluoroethylene, and an electrode interface, a temperature measuring hole, a gas path interface and a vacuum pumping port are reserved in the cavity. The gas path interface is connected to an argon purifier, and the vacuum pumping port is connected to a vacuum pump. The armored heating wire is wrapped around the outside and matched with the embedded K-type thermocouple inside the cavity; the two metal plates are fixed in the center of the cavity in a parallel manner with an insulating bracket, wherein the lower plate is connected to the external ground electrode through the cavity insulating sleeve through the grounding wire, and the other plate is connected to the external ground electrode through the cavity insulating sleeve. The wires of the metal plates are connected to the high-voltage power supply through insulating sleeves through the cavity wall, and the gas line interface is connected to a vacuum pump. The mold is placed between the two plates. Specifically, the upper mold and the lower mold are 10 mm apart, and both are fixed in the cavity by insulating brackets. The cavity surface of the upper mold faces the lower plate with a minimum distance of 4 mm between them, and the cavity surface of the lower mold faces the upper plate with a minimum distance of 4 mm between them. A 0.1 mm thick copper sheet is fixed to the lower plate at one end, and the other end is pressed against the non-coated surface of the upper mold with an insulating clamp. Start the vacuum pump and pump the pressure in the cavity to 1×10 -3Pa, maintain for 5 minutes to eliminate residual air, turn off the vacuum pump and introduce argon until the pressure in the cavity is 20Pa, stabilize for 10 minutes, increase the temperature to 400℃ at a rate of 10℃ / min, keep the temperature constant for 10 minutes, start the high-voltage power supply, set the voltage to 30kV, and continue the treatment for 20 minutes. After the treatment is completed, turn off the high-voltage power supply, keep the argon flowing, wait for the mold to cool naturally to room temperature, open the cavity and take out the mold.

[0038] Example 7 This embodiment is basically the same as embodiment 5, except that step (3) uses a closed cavity made of polytetrafluoroethylene, and an electrode interface, a temperature measuring hole, a gas path interface and a vacuum pumping port are reserved in the cavity. The gas path interface is connected to an argon purifier, and the vacuum pumping port is connected to a vacuum pump. The armored heating wire is wrapped around the outside and matched with the embedded K-type thermocouple inside the cavity; the two metal plates are fixed in the center of the cavity in a parallel manner with an insulating bracket, wherein the lower plate is connected to the external ground electrode through the cavity insulating sleeve through the grounding wire, and the other plate is connected to the external ground electrode through the cavity insulating sleeve. The wires of the metal plates are connected to the high-voltage power supply through insulating sleeves through the cavity wall, and the gas line interface is connected to a vacuum pump. The mold is placed between the two plates. Specifically, the upper mold and the lower mold are 10 mm apart, and both are fixed in the cavity by insulating brackets. The cavity surface of the upper mold faces the lower plate with a minimum distance of 4 mm between them, and the cavity surface of the lower mold faces the upper plate with a minimum distance of 4 mm between them. A 0.1 mm thick copper sheet is fixed to the lower plate at one end, and the other end is pressed against the non-coated surface of the upper mold with an insulating clamp. Start the vacuum pump and pump the pressure in the cavity to 1×10 -3 Pa, maintain for 5 minutes to eliminate residual air, turn off the vacuum pump and introduce argon until the pressure in the cavity is 30Pa, stabilize for 10 minutes, increase the temperature to 200℃ at a rate of 10℃ / min, keep the temperature constant for 10 minutes, start the high-voltage power supply, set the voltage to 30kV, and continue the treatment for 20 minutes. After the treatment is completed, turn off the high-voltage power supply, keep the argon flowing, wait for the mold to cool naturally to room temperature, open the cavity and take out the mold.

[0039] Example 8 This embodiment is basically the same as embodiment 5, except that it further includes step (4), specifically: placing the mold after electric field treatment into a vacuum annealing furnace, closing the furnace door, starting the vacuum pump, and evacuating to 1×10 -3 Pa, heat to 300℃ at a rate of 5℃ / min, keep warm for 10min, continue to heat to 350℃ at a rate of 3℃ / min, keep warm for 2.5h, cool to room temperature with the furnace, open the furnace door and take out the mold.

[0040] Example 9 This embodiment is basically the same as embodiment 8, except that in step (4), the mold after electric field treatment is placed in a vacuum annealing furnace, the furnace door is closed, the vacuum pump is started, and the vacuum is pumped to 1×10 -3 Pa, heat to 200℃ at a rate of 5℃ / min, keep warm for 10min, continue to heat to 300℃ at a rate of 3℃ / min, keep warm for 3h, cool to room temperature with the furnace, open the furnace door and take out the mold.

[0041] Example 10 This embodiment is basically the same as embodiment 8, except that in step (4), the mold after electric field treatment is placed in a vacuum annealing furnace, the furnace door is closed, the vacuum pump is started, and the vacuum is pumped to 1×10 -3 Pa, heat to 300℃ at a rate of 5℃ / min, keep warm for 10min, continue to heat to 400℃ at a rate of 3℃ / min, keep warm for 2h, cool to room temperature with the furnace, open the furnace door and take out the mold.

[0042] Example 11 This embodiment is basically the same as embodiment 8, except that, in step (2), the Cr target is turned on, Ar gas is introduced, and the working pressure in the vacuum chamber is maintained at 0.4 Pa. When the Cr target power is 200 W and the bias voltage is -50 V, a Cr transition layer with a thickness of 1.1 μm is deposited for 30 minutes; the Cr target is kept on, 20 sccm of Ar is kept introduced, and 10 sccm of N2 is introduced into the vacuum chamber, and the pressure in the vacuum chamber is maintained at 0.4 Pa. When the Cr target power is 200 W and the bias voltage is -8 0V, deposit for 60min to obtain a CrN layer with a thickness of 3.2μm; turn off the Cr target, turn on the TiAl target, introduce 20sccm of Ar and 30sccm of N2, and maintain the working pressure in the vacuum chamber at 0.4Pa. At the TiAl target power of 300W and the bias voltage of -100V, deposit for 90min to obtain a TiAlN layer with a thickness of 4.9μm; after the deposition is completed, turn off the target power and gas, maintain the vacuum state of the vacuum chamber, cool it to below 100℃ with the furnace, fill it with Ar gas to normal pressure, and take out the mold.

[0043] Example 12 This embodiment is basically the same as embodiment 8, except that, in step (2), the Cr target is turned on, Ar gas is introduced, and the working pressure in the vacuum chamber is maintained at 0.4 Pa. When the Cr target power is 300 W and the bias voltage is -100 V, a Cr transition layer with a thickness of 3.4 μm is deposited for 30 minutes; the Cr target is kept on, 20 sccm of Ar is introduced, and 10 sccm of N2 is introduced into the vacuum chamber, and the pressure in the vacuum chamber is maintained at 0.4 Pa. When the Cr target power is 300 W and the bias voltage is -1 20V, deposition for 60min to obtain a CrN layer with a thickness of 5.8μm; turn off the Cr target, turn on the TiAl target, introduce 20sccm of Ar and 30sccm of N2, and maintain the working pressure in the vacuum chamber at 0.4Pa. At the TiAl target power of 500W and the bias voltage of -150V, deposition for 90min to obtain a TiAlN layer with a thickness of 7.2μm; after the deposition is completed, turn off the target power and gas, maintain the vacuum state of the vacuum chamber, cool it to below 100℃ with the furnace, fill it with Ar gas to normal pressure, and take out the mold.

[0044] Comparative Example 1 This comparative example provides a method for preparing the surface coating of the high-pressure hot-pressing mold, comprising the following steps: (1) The H13 steel mold substrate was subjected to supersonic sandblasting with 20-40 μm Al2O3 abrasive, 0.6 MPa pressure, and 80 nm spray distance. The treatment time was 3 min, and the surface roughness of the H13 steel mold was obtained to be Ra=5-8 μm. Then, a 1 mm diameter WC-Co projectile was used, with a frequency of 20 kHz and an amplitude of 30 μm, for 10 min to obtain a nanocrystalline layer H13 steel mold with a surface of 50-100 nm. The treated H13 steel mold was fixed on the substrate holder of the vacuum chamber and connected to the cathode of the bias power supply. The Cr target and TiAl target required for coating were respectively fixed on the cathode of the evaporation source, and the distance between the mold and the target was 10 cm. At the same time, a mask was used to fit the non-cavity surface of the mold, and the base of the evaporation source was connected to the anode. The vacuum chamber door was closed, and the mechanical pump was started to evacuate the air to a pressure less than 0.1 Pa. Then the molecular pump was turned on to evacuate the air to a background vacuum less than 3×10 -4 Pa; turn on the substrate heating stage, raise the temperature to 300℃, and keep it warm for 30 minutes; then introduce Ar gas with a flow rate of 15sccm, adjust the vacuum chamber pressure to 0.4Pa; apply a negative bias voltage of 400V to the mold, turn on the auxiliary anode, and generate Ar + Particles bombard the mold surface and etch for 20 minutes; (2) Turn on the Cr target, introduce Ar gas, and maintain the working pressure in the vacuum chamber at 0.4 Pa. At the Cr target power of 250 W and the bias voltage of -80 V, deposit for 30 minutes to obtain a Cr transition layer with a thickness of 2.3 μm; continue to keep the Cr target open, keep introducing 20 sccm of Ar, and introduce 10 sccm of N2 into the vacuum chamber, maintain the pressure in the vacuum chamber at 0.4 Pa, at the Cr target power of 250 W and the bias voltage of -100 V, and deposit for 60 minutes to obtain To a CrN layer with a thickness of 4.6μm; turn off the Cr target, turn on the TiAl target, introduce 20sccm of Ar and 30sccm of N2, and maintain the working pressure in the vacuum chamber at 0.4Pa. At the TiAl target power of 400W and the bias voltage of -120V, deposit for 90min to obtain a TiAlN layer with a thickness of 6.1μm; after the deposition is completed, turn off the target power and gas, maintain the vacuum state of the vacuum chamber, cool it to below 100℃ with the furnace, fill it with Ar gas to normal pressure, and take out the mold.

[0045] Performance testing Adhesion test: The adhesion between the coating and the substrate of the hot pressing molds prepared in Examples 1 to 12 and Comparative Example 1 was tested using a WS-2005 coating adhesion automatic scratch tester. The test results are recorded in Table 1.

[0046] Microhardness test: The microhardness of the coatings of the hot pressing molds prepared in Examples 1 to 12 and Comparative Example 1 was tested using a HWV-IT microhardness tester. The test results are recorded in Table 1.

[0047] Wear resistance test: The coatings of the hot pressing molds prepared in Examples 1 to 12 and Comparative Example 1 were tested using an HT-500 high temperature friction and wear tester. The test results are recorded in Table 1.

[0048] Service life: The hot pressing molds prepared in Examples 1-12 and Comparative Example 1 were heated to 1000°C and kept warm for 5 minutes, then taken out and quickly placed in 25°C water for cooling. This process was repeated until 5% of the coating on the mold surface fell off. At this time, the coating was determined to have failed, and the number of cycles was recorded in Table 1.

[0049] Table 1 Performance test data of high pressure hot pressing die surface coating in Examples 1-12 and Comparative Example 1

[0050] Refer to Table 1 and Figure 1-2 , combined with Examples 1-12 and Comparative Example 1, it can be seen that Figure 1 It can be seen from the figure that the coating structure is dense, the boundaries between layers are fuzzy at the interface, showing a "sawtooth" fuzzy transition, compared with the traditional coating interface that is not treated with a high voltage electric field and presents a "straight line" mutation boundary. Figure 2 As can be seen in the figure, the Cr-CrN-TiAlN composite coating, after high-voltage electric field treatment, primarily contains N, Cr, Ti, and Al elements. While the electric field promotes the diffusion of Fe atoms from the substrate into the Cr layer, the diffusion range is limited and below the detection threshold, resulting in the absence of Fe in the EDS image above. This is because, by subjecting the coated mold to high-voltage electric field treatment, the electric field force not only drives the directional migration of charged defects within the coating, releasing residual stress, but also promotes the diffusion of interface elements, forming a transition layer with a gentle composition gradient, thereby reducing interfacial brittleness caused by stress concentration and sudden composition changes. Furthermore, the electric field optimizes the coating's microstructure, increasing density by reducing porosity and refining grains, enhancing mechanical engagement, and potentially promoting the formation of stronger chemical bonds at the interface, increasing the bonding strength between the substrate and coating, thereby extending the mold's service life.

[0051] Referring to Table 1, in combination with Examples 1 and 4, it can be seen that the present application chooses to carry out the treatment in an inert atmosphere during the high-voltage electric field treatment, which effectively isolates oxygen and impurities, prevents oxidation reactions of easily oxidizable elements (such as Al, Ti, Cr) in the coating and the H13 steel substrate, and avoids the formation of a brittle oxide layer that hinders element diffusion; at the same time, it can inhibit impurities such as moisture and CO2 from reacting with the coating or the substrate to form a brittle phase, thereby ensuring the purity of the interface; in addition, the inert gas has high ionization energy, can stabilize the high-voltage electric field distribution, reduce the damage to the coating caused by arc discharge, and ultimately improve the overall performance of the mold.

[0052] Referring to Table 1, in combination with Examples 4 and 5, it can be seen that in the present application, the high-voltage electric field treatment is carried out at 300°C. This temperature is not only lower than the tempering temperature of H13 steel, avoiding softening of the substrate due to overheating (reducing the supporting strength of the substrate), but also lower than the significant oxidation temperature of TiAlN. At the same time, the low-temperature heat treatment assisted by the electric field can relieve the internal stress generated during the coating deposition process, refine the grains, and thus improve the hardness, wear resistance and anti-spalling properties of the coating.

[0053] Referring to Table 1, combined with Examples 5 and 8, it can be seen that in the present application, after the high-voltage electric field treatment, the mold is further annealed and strengthened. The annealing treatment can not only eliminate the residual stress caused by the lattice distortion generated by the high-voltage electric field through atomic thermal motion, thereby avoiding interface cracking caused by stress concentration; it can also promote the transformation of the metastable phase formed by the high-voltage electric field into an equilibrium phase, thereby enhancing the structural matching between the coating and the substrate; at the same time, with the help of thermal drive, the diffusion channel formed by the electric field pretreatment is further strengthened, so that the elements diffuse more fully, the interface metallurgical bonding is enhanced, and the comprehensive performance of the mold is further improved.

[0054] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A method for preparing a surface coating of a high-pressure hot-pressing mold, characterized in that: The following steps are involved: (1) Pretreatment of H13 steel substrate; (2) Magnetron sputtering was used to deposit Cr layer, CrN layer and TiAlN layer in sequence on the pretreated H13 steel surface to form a Cr~CrN~TiAlN composite coating; (3) The coated substrate is placed in a high-voltage electric field for treatment to obtain a high-pressure hot pressing mold surface coating.

2. The method for preparing a high-pressure hot-pressing mold surface coating according to claim 1, characterized in that: Step (3) is specifically as follows: placing the coated substrate in a high-voltage electric field consisting of two parallel metal plates, one of which is grounded and the other is connected to a high-voltage electric field generator, and the distance between the coating surface on the substrate and the metal plates is greater than 1 mm.

3. The method for preparing a high-pressure hot-pressing mold surface coating according to claim 2, characterized in that: The distance between the coating surface on the substrate and the metal plate is 2-4 mm, the voltage of the high-voltage electric field is 5-50 kV, and the treatment time is 5-30 minutes.

4. The method for preparing a high-pressure hot-pressing mold surface coating according to claim 1, characterized in that: In step (3), the processing environment during the high-voltage electric field treatment is an inert gas atmosphere with a gas pressure of 20~30Pa.

5. The method for preparing a high-pressure hot-pressing mold surface coating according to claim 4, characterized in that: The treatment temperature during the high-voltage electric field treatment is 200-400°C.

6. The method for preparing a high-pressure hot-pressing mold surface coating according to claim 1, characterized in that: In step (1), the specific method of pre-treating the H13 steel substrate is: pre-treating the surface of the H13 steel substrate by supersonic sandblasting, ultrasonic shot blasting and plasma cleaning in sequence.

7. The method for preparing a high-pressure hot-pressing mold surface coating according to claim 6, characterized in that: It also includes vacuum annealing strengthening treatment, specifically: the mold treated with a high voltage electric field is treated at 300-400°C in an inert atmosphere for 2-3 hours.

8. The method for preparing a high-pressure hot-pressing mold surface coating according to claim 1, characterized in that: In step (2), the thickness of the Cr layer is 1.1-3.4 μm, the thickness of the CrN layer is 3.2-5.8 μm, and the thickness of the TiAlN layer is 4.9-7.2 μm.

9. The method for preparing a high-pressure hot-pressing mold surface coating according to claim 1, characterized in that: In step (2), the power of the Cr target used in the magnetron sputtering method is 200~300W, the power of the TiAl target is 300~500W, and the distance between the target and the substrate is 8~12cm; the substrate temperature is 200~400℃, and the substrate bias is -50~-100V when depositing the Cr layer, the substrate bias is -80~-120V when depositing the CrN layer, and the substrate bias is -100~-150V when depositing the TiAlN layer.

10. High-pressure hot-pressing mold surface coating, characterized in that: The surface coating of the high-pressure hot-pressing mold is prepared by the method for preparing the surface coating of the high-pressure hot-pressing mold according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-voltage electric field treating apparatus for preparing area vertically aligned nano carbon tube

    CN101254915A

  • AlTiN-AlCrN super hard nano multilayer composite coating hob and preparation method thereof

    CN102922052A

  • AlTiN coating and preparation method thereof

    CN108796432A

  • Multilayer multi-element nano composite self-lubricating hard coating and preparation method and application thereof

    CN108866480A

  • Protective coating capable of resisting erosion of solid particles and preparation method of protective coating

    CN114086117A